Development of a Flooded Forest Anthropization Index (FFAI) applied to Amazonian areas under pressure from different human activities. (January 2015) - Magalhães, José Leonardo Lima; Lopes, Maria Aparecida; Queiroz, Helder Lima de
Highlights: FFAI enables assessment of human disturbance at a local scale in floodplain forest. At a local level, FFAI is sensitive to different types of disturbance. At a local level, FFAI assesses the strength of each type of impact. A useful tool for decision makers in choosing priority areas for intervention. Abstract: The floodplain forests in the Amazon basin suffer from the continued exploitation of natural resources and, after being disturbed, show slow and sometimes irreversible recovery. Our goal was to create an index that could be used to assess the relative level of human disturbance in floodplain forests and determine the relative importance of different types of disturbance on a given site and between sites. The index proposed here (Flooded Forest Anthropization Index – FFAI) assesses human disturbance on a local scale and is composed by 15 indicators divided into three groups that represent different levels of impact: (1) simplification of ecosystems and reduction of local diversity; (2) ecosystem replacement/destruction; (3) disturbances with the potential to impact the ecosystem in both ways. The FFAI proved to be robust and revealed a wide range of values in the evaluated landscapes. The sites classified a priori as more anthropogenic showed significantly higher FFAI values than the less anthropogenic ones (0.14 ± 0.05 and 0.08 ± 0.02, respectively, F  = 18.9, df  = 19, p  < 0.0001). The FFAI enabled a comprehensive assessment of human disturbance on a local scale in Amazonian floodplain forests and can be a useful tool for decision makers in choosing priority areas for interventions and for targeting the type of intervention that must be carried out. Although specific to floodplains, the index can be adjusted to be used in other ecosystems.